Reliability based design optimization using a genetic algorithm: application to bonded thin films areas of copper/polypropylene - Corso,Leandro Luis (Universidad de Tarapacá., 2016)
In the present study, a methodology is appliedfor system reliability based design optimization (RBDO) to thin copper films that are deposited on flat surfaces of polypropylene polymer. The input data of the design of such polymer-metal joint was determined by the necessary normal stress to detach the copper film from the substrate of polypropylene by different forces and interface areas, obtained from uniaxial tensile test. The RBDO methodology was implemented in order to find the smallest bonding area required to assure different reliability levels, minimizing the detaching probability and cost (lower amount of the metallic film). The reliability level is treated as input data and considered as a constraint in the optimization problem. The used optimization methodology is the Genetic Algorithm (GA). This choice is due to the fact that GA presents good behavior when dealing with functions that may exhibit nonlinear behavior. The results shows that the applied methodology is efficient and it is concluded that high reliability requirements might impose larger areas. In the case of 98% of the reliability cases in not detaching the thin film, the resulted bonded area is 3.18 greater than the initial value without safety requirements.